BUDAYA MAIN HAKIM SENDIRI (EIGENRECHTING ) TERHADAP PELAKU KEJAHATAN YANG TERTANGKAP - Lukman Hakim (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2016)
Humans as social beings who have always been drivento do social interaction with other human beings, where theinteraction of each had interests. They will further maintain theappropriate danmembela its own interests than the interests ofothers. So there are times when the interests collided andcaused chaos in the community. It is need for rules/norms orguidelines so that chaos does not arise in the midst of thecommunity. The norms that could be written or unwritten law. Ifthere is a deed that deviate from societal norms of the law, thenthe community will call it as an act of crime. We often see thatwrongdoers caught tidakdiselesaikan and processed inaccordance with the applicable law, the akantetapi resolved bymainhakim himself. It shows because of the weakness of theexisting law, the less the responsifnya officers of a crime in thiscase reporters.